EMPOWERING EFL WRITING: TEACHERS’ VOICES ON CURRICULUM INNOVATION - Muaripin, Ary Maulana; Perda, Meri; Sajidin, Sajidin; Sulaeman, Dedi (Language Literacy: Journal of Linguistics, Literature, and Language Teaching, 2025)
This article explores the contribution of curriculum innovation in writing instruction in English as a Foreign Language (EFL) at junior high schools in Indonesia. Through a qualitative study design, employing semi-structured interviews with EFL teachers, the research investigates their beliefs, implementation models, and challenges encountered during curriculum changes. The findings reveal that teachers generally perceive curriculum innovation as beneficial and educative. However, the lack of resources, inadequate training, and limited institutional support are significant barriers that hinder the effective implementation of the innovations. Teachers reported that these constraints impede their ability to fully integrate and apply the new curriculum effectively in the classroom. In response, policy recommendations are made, emphasizing the importance of providing sufficient resources, ongoing professional development, and stronger institutional support. These actions would help bridge the gap between curriculum innovations and the practical realities of classroom teaching, enabling teachers to optimize the benefits of curriculum changes in EFL instruction.